Automatic Foldron T-Shirt With Proportional Integral Derivative method and M5Stack for IoT-Server - Jonggo’man, Yunus Baweng (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
The process of folding clothes is one of the activities carried out in the household, and the laundry business is one of the micro-enterprises that are mushrooming at this time. Business actors use many strategies to increase productivity and customer satisfaction. Based on research, the process of ironing and folding clothes is a process that takes a long time compared to the washing and drying process, so a method or tool is needed to make folding clothes more practical. An automatic Foldron T-Shirt is the perfect solution to make folding and ironing clothes more manageable and time-efficient. This tool is equipped with a servo motor that moves the folding board and a steam iron designed so that the user only needs to control the clothes once and simply press one button; the clothes will fold, and the iron themselves will be neatly arranged. The PID method uses an ultrasonic sensor to measure the speed distance of the wiper motor, which is used to run the steam iron so that it can stop appropriately at the end of the table. The output of this ultrasonic sensor is used as the input (set point) of the PID controller applied to the tip so that the movement of the motor can adjust its speed. Moreover, the M5Stack, equipped with 12 Channel Servo, is used to drive the servo motor on the Application Server, making it more dynamic and flexible.